2010
DOI: 10.1297/cpe.19.101
|View full text |Cite
|
Sign up to set email alerts
|

Initial Treatment of Pediatric Graves' Disease with Methimazole: A Retrospective Follow-up Study

Abstract: Antithyroid drugs are widely used in the therapy of Graves’ disease (GD), and methimazole (MMI) is preferred for treatment of pediatric GD. The recommended initial dosage of MMI is 0.5–1.0 mg/kg/d for pediatric GD, although there are few studies on the optimal MMI dosage for initial treatment in children. We retrospectively compared the efficacy of different doses of MMI in 35 children with GD. Eight children were excluded due to lack of follow-up, etc. The remaining 27 children were divided into a high-dose g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Slyper et al 26) reported that an initial MMI dose >0.5 mg/kg was more effective for children and adolescents with GD than doses <0.5 mg/kg, without considering GD severity. Matsushita et al 23) reported that the mean time to the normalization of fT4 levels did not differ significantly between groups using a high (≥0.7 mg/kg/day) and low (<0.7 mg/kg/day) dose of MMI, and their groups did not differ significantly in GD severity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Slyper et al 26) reported that an initial MMI dose >0.5 mg/kg was more effective for children and adolescents with GD than doses <0.5 mg/kg, without considering GD severity. Matsushita et al 23) reported that the mean time to the normalization of fT4 levels did not differ significantly between groups using a high (≥0.7 mg/kg/day) and low (<0.7 mg/kg/day) dose of MMI, and their groups did not differ significantly in GD severity.…”
Section: Discussionmentioning
confidence: 97%
“…In Japan, Minamitani et al 14) recommended starting doses of 0.25-1.0 mg/kg/day in children, which is lower than the dose generally used in Japan (0.5-1.0 mg/kg/day). 23) There is no definitive guideline for the initial MMI dose for childhood-onset GD in Korea. Since the recent designation of AE reduction as the highest priority, ATD doses have tended to decrease.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Anti-thyroid medication was discovered in 1940 and the first drug that used was Propylthiouracil (PTU), but now the drug that often used in children is Methimazole (MMI). [5] The response to methimazole or radioiodine therapy for Graves' disease can be assessed by a decrease in TSI levels which correlates with an increase in Thyroid Stimulating Hormone (TSH) levels. [5] Studies in the adult population concluded that in patients with new-onset Graves' disease, high thyroxine levels, high thyrotropin binding inhibitory immunoglobulin (TBII), and absence or low goiter have responded well to methimazole therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[5] The response to methimazole or radioiodine therapy for Graves' disease can be assessed by a decrease in TSI levels which correlates with an increase in Thyroid Stimulating Hormone (TSH) levels. [5] Studies in the adult population concluded that in patients with new-onset Graves' disease, high thyroxine levels, high thyrotropin binding inhibitory immunoglobulin (TBII), and absence or low goiter have responded well to methimazole therapy. [6] Other studies have shown that initial TRAb levels are better predictive of remission in Graves' disease.…”
Section: Introductionmentioning
confidence: 99%